Designing the Development of Canva Application-Based Audio-Visual Teaching Materials on the Material "Point to Point Distance" for High School Students - Viky Risnanda Arif; Rani Darmayanti; Usmiyatun Usmiyatun (JEMS: Jurnal Edukasi Matematika dan Sains, 2023)
Mathematics learning is not optimal because of limited learning media. Most teachers only rely on manual materials and exercises that are too strict. The purpose of this research is to create an audiovisual learning media based on the Canva application for class XII learning. This type of research is media development based on the four-D development model. Due to the limitations of researchers, the development of this media has only reached the development stage. The subjects of this study were 2 media experts, 2 material experts, 2 practitioners and 25 students. Data collection methods in this study are observation methods, interview methods, and questionnaire methods. The data were analyzed qualitatively and quantitatively using the average formula to obtain an average efficacy score. As a result, the audiovisual media based on the Canva application on the topic "Distance point to point" achieved a relevance score of 4.53 for content experts and 4.65 for media experts